Analisis Self-Care Emosional Mahasiswa PGSD dalam Menghadapi Tugas Perkuliahan yang Menumpuk - Tria Putri Salsabilla; Yuni Ariesty; Jesi Alexander Alim; Mitha Dwi Anggriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the emotional self-care practices of PGSD (Elementary School Teacher Education) fifth-semester students at the Faculty of Teacher Training and Education, in dealing with overwhelming academic assignments. Using a descriptive qualitative method through an online survey of 10 students. The findings reveal that most students experience high emotional pressure, including stress, anxiety, and mental fatigue. The coping strategies applied are predominantly emotion-focused, such as positive distraction, relaxation, and religious activities. Social support from peers, family, and lecturers was found to be an important factor in reducing emotional distress, although self-care practices were often hindered by limited time and lack of consistency. Emotional conditions directly affected learning motivation, with positive emotions enhancing focus and enthusiasm, while negative emotions decreased concentration and encouraged procrastination. These findings highlight that emotional self-care plays a crucial role in maintaining students’ mental health and motivation, yet its implementation requires institutional support through counseling services and better-structured academic workload management.